The Data-Driven Approach in Transitioning Organizational Strategies and Capabilities: Insights from Indonesia's National Narcotics Agency - Komang Ari Widani; Abdullah Hasan; Benny Ranti; Muhammad Rifki Shihab; Widha Utami Putri; Syam Fikry Mardiansyah (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
Anti-narcotics prevention measures, such as urine sampling of suspect offenders, citizen reporting of suspect narcotic activities, public education, or legal consultations used to be performed at provincial and city levels. To improve effectiveness and efficiency, Indonesia’s National Narcotics Agency (Badan Narkotika Nasional or BNN) centralized such initiatives by introducing BOSS (BNN One-Stop Service), an integrated service information system provided to the public. However, at present data generated by BOSS has not been fully exploited in the design of BNN strategy. The objective of this study is to explore the untapped potential of BOSS data to improve BNN strategy and capabilities, focusing on preventing and eradicating narcotics abuse. The methodology used is descriptive qualitative, with data collection through document analysis and interviews. This study is expected to provide a preliminary interpretation of how BOSS data can improve BNN's ability to fight narcotics abuse more effectively and efficiently. The results of the study show that the integration of BOSS data can significantly optimize the efficiency, analytical capabilities, and responsiveness of BNN in dealing with narcotics abuse, showing that the use of strategic data from BOSS is the key to BNN's digital transformation for a more effective narcotics prevention and eradication strategy.